The Impact of Social Media on the Decision to Use Telemedicine Among Batam’s Citizen - Edy Yulianto Putra; Jessy Jessy (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2022)
Online consultation or better known as Telemedicine is a technological breakthrough that centered on medical subject, this activity used the internet as their communication media. One of the biggest market potential to promote the telemedicine is social media. This study discusses the influence and impact of surveillance, social interaction, information sharing, entertainment and social media richness towards purchase intention with brand equity as the mediation. The method used in this study is correlational quantitative method with 400 participating respondents and the questionnaire distribution is carried out with the Google Form as a data collection. The outcome of this study revealed that the relationship between surveillance, social interaction, information sharing, entertainment, social media richness and purchase intention with brand equity as the mediating role is significant and positive.